What to grow for a climate resilient garden - Rasmussen, Amanda M. C.; Royal Horticultural Society (Great Britain) (London : Greenfinch, 2025)
'What to Grow for a Climate Resilient Garden' urges green-thumbed readers that are conscious of the environment to think deeper about the impact of maintaining a thriving garden on the future of the planet, and vice versa. With easy, practical ideas, it is the ideal book for experienced gardeners and a growing environmentally-inclined public looking for ways to make a difference. Eminent plant expert Dr Amanda Rasmussen explains what makes particular plants suited to certain conditions, along with easy-to-implement ideas for forward-thinking gardeners.
Published in association with the Royal Horticultural Society.
Includes bibliographical references and index.
Keywords: Gardening; Jardinage; gardening; Gardening